Pengaruh Manajemen Laba dan Siklus Hidup Perusahaan terhadap Penghindaran Pajak Dengan Pertumbuhan Penjualan Sebagai Mediator - Nuroniyyah, Lailatun; Febriani, Eka; Dhanny, Omar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This research is intended to analyze and prove the effect of earnings management and the company's life cycle on tax avoidance practices that occurred during the Covid-19 outbreak with sales growth as a mediator for companies in the food and beverage sub-sector registered on the Indonesia Stock Exchange for the 2020-2021 period. A sampling of data using purposive sampling method and the data obtained for snsy did is as much as 38 data. Testing the data shows that earnings management has an influence on sales growth, sales growth has an influence on tax evasion, and earnings management does not have a direct effect on tax evasion but has an indirect effect on tax evasion through sales growth. The company's life cycle has no influence on sales growth and tax avoidance